2015
DOI: 10.3109/00498254.2015.1072253
|View full text |Cite
|
Sign up to set email alerts
|

Species differences in metabolism of EPZ015666, an oxetane-containing protein arginine methyltransferase-5 (PRMT5) inhibitor

Abstract: 1. Metabolite profiling and identification studies were conducted to understand the cross-species differences in the metabolic clearance of EPZ015666, a first-in-class protein arginine methyltransferase-5 (PRMT5) inhibitor, with anti-proliferative effects in preclinical models of Mantle Cell Lymphoma. EPZ015666 exhibited low clearance in human, mouse and rat liver microsomes, in part by introduction of a 3-substituted oxetane ring on the molecule. In contrast, a higher clearance was observed in dog liver micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
1
12
1
1
Order By: Relevance
“…AZD1979 is a melanin-concentrating hormone receptor 1 antagonist containing a spiro oxetanylazetidinyl moiety as a building block. Contrary to the reported P450-mediated oxidative ring scission of oxetanes (Stepan et al, 2011;Rioux et al, 2016), our studies have shown that the net addition of water to AZD1979 to form M1 is a non-P450 enzyme-catalyzed reaction. Although the final diol products from these oxetanes are analogous, the mechanisms that lead to their formation are clearly different.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…AZD1979 is a melanin-concentrating hormone receptor 1 antagonist containing a spiro oxetanylazetidinyl moiety as a building block. Contrary to the reported P450-mediated oxidative ring scission of oxetanes (Stepan et al, 2011;Rioux et al, 2016), our studies have shown that the net addition of water to AZD1979 to form M1 is a non-P450 enzyme-catalyzed reaction. Although the final diol products from these oxetanes are analogous, the mechanisms that lead to their formation are clearly different.…”
Section: Discussioncontrasting
confidence: 46%
“…However, only a limited number of studies have been published on the metabolism of oxetanes. Rioux et al (2016) reported a CYP2D-and CYP3A-mediated oxidative ring scission pathway of a 3-substituted dx.doi.org/10.1124/dmd.116.071142. s This article has supplemental material available at dmd.aspetjournals.org.…”
Section: Introductionmentioning
confidence: 99%
“…Further PK studies revealed that at 100 mg/kg in mouse, the unbound plasma concentration was equivalent to or above, the methyl mark IC 90 for a period of 12 h, thus suggesting that BID dosing of EPZ015666 could effectively inhibit PRMT5 in vivo (Figure 4). Additional species PK and ADME characterization data on EPZ015666 were reported by Rioux et al 17 In summary, we have outlined the medicinal chemistry strategies employed in the optimization of a submicromolar HTS hit (1) to the selection of a potent in vivo tool compound to evaluate the pharmacology of PRMT5 inhibition. Early SAR exploration around the THIQ motif confirmed the contribution of the cation−π interaction with cofactor SAM and was thus retained within the series as a key binding interaction.…”
mentioning
confidence: 99%
“…Accordingly, the symmetric methylation level in the xenograft tumors was decreased in a dose-dependent manner. A following study [109] reports that EPZ015666 exhibits low clearance in human, mouse and rat liver microsomes and higher clearance in dog liver microsomes as well as hepatocytes. This study provides important information about similarity of the metabolism profiles between different organisms and human, which may facilitate the transition from preclinical models to human test.…”
Section: Prmt5-specific Inhibitorsmentioning
confidence: 99%